Analisis kelayakan bisnis pada bmt-ugt nusantara: Strategi untuk menjamin keberlanjutan - Ummi, Laely saidatul (Maliki Interdisciplinary Journal, 2025)
Baitul Maal wa Tamwil (BMT) UGT Nusantara is a sharia microfinance institution that uses a fair and transparent financial system to support the economic growth of the community. The purpose of this study is to evaluate the feasibility of the BMT-UGT Nusantara business by looking at various aspects, such as law, market, technology, and management. The goal is to find strategies that support sustainability. The results of the analysis show that BMT UGT Nusantara has very positive prospects for further development. This is supported by the existence of a strong legal basis and in accordance with sharia principles, broad market potential with an increasing level of need for sharia financial services, a targeted marketing strategy that is able to reach wider levels of society, and the use of digital technology that helps improve efficiency and service